Agnes of God - Fonda, Jane, 1937-; Bancroft, Anne, 1931-2005.; Tilly, Meg.; Palmer, Patrick; Jewison, Norman, 1926-; Pielmeier, John.; Columbia Pictures Corporation; Columbia TriStar Home Entertainment (Firm) (Culver City, Calif. : Columbia TriStar Home Entertainment, 2002)
When, at an isolated convent, the infant of a young nun is found strangled, a court-appointed psychiatrist must decide if the devout but troubled girl is fit to stand trial.
DVD; widescreen (1.85:1), Dolby surround.
English or dubbed French; optional subtitles in English, Chinese, French, Korean, Portuguese or Spanish; closed-captioned.
Jane Fonda, Anne Bancroft, Meg Tilly.
Director of photography, Sven Nykvist ; editor, Antony Gibbs ; music, Georges Delerue.
Originally produced as a motion picture in 1985.
Based upon the stage play by John Pielmeier.
Keywords: Nuns -- Drama; Miracles -- Drama; Thrillers (Motion pictures); Miracles; Nuns; Thrillers (Motion pictures); Crime films; Detective and mystery films; Feature films; Fiction films; Video recordings for the hearing impaired; Feature films; Suspense films; Mystery films; Thriller -- Feature; Mystery -- Feature; Crime -- Feature; Drama